Multicomponent synthesis of sulfonamides from triarylbismuthines, nitro compounds and sodium metabisulfite in deep eutectic solvents. Issue 15 (10th July 2019) - Marset, Xavier; Torregrosa-Crespo, Javier; Martínez-Espinosa, Rosa M.; Guillena, Gabriela; Ramón, Diego J.
Abstract : A sustainable synthesis of sulfonamides using a copper-catalysed process starting from triarylbismuthines, Na2 S2 O5 and nitro compounds in a Deep Eutectic Solvent (DES) as a reaction medium is described. Abstract : A sustainable synthesis of sulfonamides using a copper-catalysed process starting from triarylbismuthines, Na2 S2 O5 and nitro compounds in a Deep Eutectic Solvent (DES) as a reaction medium is described. Thus, triarylbismuthines are used as reagents for the incorporation of SO2 into organic motifs. The bismuth salts formed as by-products can be easily removed from the crude reaction mixture by precipitation with water, while the use of volatile organic compounds (VOCs) as solvents can be avoided in the entire process. The eutectic mixture employed as the solvent is fully characterised, with the preliminary results proving its low toxicity. The designed DES also allows for a novel multicomponent reaction which saves time and reduces purification steps, energy and cost.